Association between HIV Serostatus and premalignant cervical lesions among women attending a cervical cancer screening clinic at a tertiary care facility in southwestern Uganda: a comparative cross-sectional study - Justus Kirabira; Musa Kayondo; Stephen Mayanja Bawakanya; Edirisa Juniour Nsubuga; Fajardo Yarine; Alexcer Namuli; Rita Namugumya; Christine Hilda Natulinda; Raymond Atwine; Abraham Birungi; Henry Mark Lugobe; Leevan Tibaijuka; et al. (BMC, 2024)
Abstract Background Uganda has approximately 1.2 million people aged 15-64 years living with human immunodeficiency virus (HIV). Previous studies have shown a higher prevalence of premalignant cervical lesions among HIV-positive women than among HIV-negative women. Additionally, HIV-infected women are more likely to have human papilloma virus (HPV) infection progress to cancer than women not infected with HIV. We determined the prevalence of premalignant cervical lesions and their association with HIV infection among women attending a cervical cancer screening clinic at Mbarara Regional Referral Hospital (MRRH) in southwestern Uganda. Methods We conducted a comparative cross-sectional study of 210 women aged 22-65 years living with HIV and 210 women not living with HIV who were systematically enrolled from March 2022 to May 2022. Participants were subjected to a structured interviewer-administered questionnaire to obtain their demographic and clinical data. Additionally, Papanicolaou smears were obtained for microscopy to observe premalignant cervical lesions. Multivariate logistic regression was performed to determine the association between HIV status and premalignant cervical lesions. Results The overall prevalence of premalignant cervical lesions in the study population was 17% (n = 72; 95% C.I: 14.1-21.4), with 23% (n = 47; 95% C.I: 17.8-29.5) in women living with HIV and 12% (n = 25; 95% C.I: 8.2-17.1) in women not living with HIV (p < 0.003). The most common premalignant cervical lesions identified were low-grade squamous intraepithelial lesions (LSIL) in both women living with HIV (74.5%; n = 35) and women not living with HIV (80%; n = 20). HIV infection was significantly associated with premalignant lesions (aOR: 2.37, 95% CI: 1.27-4.42; p = 0.007). Conclusion Premalignant cervical lesions, particularly LSILs, were more common in HIV-positive women than in HIV-negative women, highlighting the need to strengthen the integration of cervical cancer prevention strategies into HIV care programs.